3.1 KiB
+++ title = "Equivalences" slug = "equivalences" date = 2023-05-06 tags = ["type-theory", "agda", "hott"] math = true draft = true +++
Imports
{-# OPTIONS --cubical #-}
open import Agda.Primitive.Cubical
open import Cubical.Foundations.Equiv
open import Cubical.Foundations.Prelude
open import Data.Bool
Bool-id : Bool → Bool
Bool-id true = true
Bool-id false = false
unap : {A B : Type} {x y : A} (f : A → B) → f x ≡ f y → x ≡ y
unap p i = ?
-- Need to convert point-wise equality into universally quantified equality?
Bool-id-refl : (x : Bool) → (Bool-id x ≡ x)
Bool-id-refl true = refl
Bool-id-refl false = refl
The equivalence proof below involves the contractibility-of-fibers definition of an equivalence. There are others, but the "default" one used by the Cubical standard library uses this.
Bool-id-is-equiv : isEquiv Bool-id
In the contractibility-of-fibers proof, we must first establish our fibers. If
we had (f : A \rightarrow B)
, then this is saying given any (y : B)
, we must
provide:
- an
(x : A)
that would have gotten mapped toy
(preimage), and - a proof that
f\ x \equiv y
These are the two elements of the pair given below. Since our function is id
,
we can just give y
again, and use the refl
function above for the equality
proof
Bool-id-is-equiv .equiv-proof y .fst = y , Bool-id-refl y
The next step is to prove that it's contractible. Using the same derivation for
y
as above, this involves taking in another fiber y_1
, and proving that it's
equivalent the fiber we've just defined above.
To prove fiber equality, we can just do point-wise equality over both the
preimage of y
, and then the second-level equality of the proof of $f\ x \equiv
y$.
In the first case here, we need to provide something that equals our x
above
when i = i0
, and something that equals the fiber $y_1$'s preimage x_1
when
i = i1
, aka y \equiv proj_1\ y_1
.
Bool-id-is-equiv .equiv-proof y .snd y₁ i .fst =
let
eqv = snd y₁
-- eqv : Bool-id (fst y₁) ≡ y
eqv2 = eqv ∙ sym (Bool-id-refl y)
-- eqv2 : Bool-id (fst y₁) ≡ Bool-id y
-- Ok, unap doesn't actually exist unless f is known to have an inverse.
-- Fortunately, because we're proving an equivalence, we know that f has an
-- inverse, in particular going from y to x, which in thise case is also y.
eqv3 = unap Bool-id eqv2
Bool-id-inv : Bool → Bool
Bool-id-inv b = (((Bool-id-is-equiv .equiv-proof) b) .fst) .fst
eqv3′ = cong Bool-id-inv eqv2
give-me-info = ?
-- eqv3 : fst y₁ ≡ y
eqv4 = sym eqv3
-- eqv4 : y ≡ fst y₁
in
eqv4 i
Now we can prove that the path is the same
\begin{CD} A @> > > B \\ @VVV @VVV \\ C @> > > D \end{CD}
A \rightarrow B
is the path of the original fiber that we've specified, which isf\ x \equiv y
C \rightarrow D
is the path of the other fiber that we're proving, which isproj_2\ y_1
So what we want now is a-b ≡ c-d
Bool-id-is-equiv .equiv-proof y .snd y₁ i .snd j =
let
a-b = Bool-id-refl y
c-d = y₁ .snd
in
?